Temperature responsiveness of gilthead sea bream bone; an in vitro and in vivo approach - Riera-Heredia, Natalia (2018)
This study aimed to characterize the molecules involved in osteogenesis in seabream and establish using in vitro/in vivo approaches the responsiveness of selected key genes to temperature. The impact of a temperature drop from 23 to 13 degrees C was evaluated in juvenile fish thermally imprinted during embryogenesis. Both, in vitro/in vivo, Fib1a, appeared important in the first stages of bone formation, and Col1A1, ON and OP, in regulating matrix production and mineralization. OCN mRNA levels were up-regulated in the final larval stages when mineralization was more intense. Moreover, temperature-dependent differential gene expression was observed, with lower transcript levels in the larvae at 18 degrees C relative to those at 22 degrees C, suggesting bone formation was enhanced in the latter group. Results revealed that thermal imprinting affected the long-term regulation of osteogenesis. Specifically, juveniles under the low and low-to-high-temperature regimes had reduced levels of OCN when challenged, indicative of impaired bone development. In contrast, gene expression in fish from the high and high-to-low-temperature treatments was unchanged, suggesting imprinting may have a protective effect. Overall, the present study revealed that thermal imprinting modulates bone development in seabream larvae, and demonstrated the utility of the in vitro MSC culture as a reliable tool to investigate fish osteogenesis.